1980
DOI: 10.1111/j.1365-2044.1980.tb05116.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to anaesthetics in 20 hospitals

Abstract: SummaryThe nitrous oxide and halothane contamination in the inspired air of anaesthetists and in the atmospheres oJ'operating theatres, anaesthetic induction and recovery rooms, were measured during normal unmodified h,orking sessions in 20 hospitals using integrated personal samplers. The nitrous oxide (and halothane) leoels ranged from < I0 to 3000 ppm ( < 0.1 to 60ppm)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The frequencies of chromosomal aberrations encountered in control populations from the literature indicates that exchange-type aberrations vary between 7 and 12 in 10 000 metaphases, with an average of 7.6 exchange events in lo4 cells. The frequency of breaks is much higher and varies from 14 to 100 x cells.z3 Our analysis of chromosome aberrations represents data obtained from 100 metaphases/ individual, so this is probably why it was not possible to detect the reported low baseline frequency of other types of aberrations in the control population.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of chromosomal aberrations encountered in control populations from the literature indicates that exchange-type aberrations vary between 7 and 12 in 10 000 metaphases, with an average of 7.6 exchange events in lo4 cells. The frequency of breaks is much higher and varies from 14 to 100 x cells.z3 Our analysis of chromosome aberrations represents data obtained from 100 metaphases/ individual, so this is probably why it was not possible to detect the reported low baseline frequency of other types of aberrations in the control population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a reduction of anaesthetic gas exposure of the operating personnel during mask induction would be absolutely essential to reduce MAK-values (Maximale Arbeitsplatzkonzentration, tolerated critical limits for inhalational anaesthetics in the operating room) to established recommended limits (NIOSH 1977). According to Davenport there is little correlation between room air turnover rate in the operating room and the occupational exposure to inhalational anaesthetics (Davenport et al 1980). Perthes first described a funnel-shaped scavenging system placed near the head of the patient with a flow of 1600 m3.h-' (Perthes 1925).…”
Section: Discussionmentioning
confidence: 99%
“…This anaesthetic may cause mild liver damage in human patients but around 1 in 30 000 develops severe liver damage due to reactive metabolites combining with liver proteins which then elicit an autoimmune response (Neuberger & Williams, 1988;Bird & Williams, 1992). In human medical practice, occupational exposure to halothane and other medical gases has long been recognised as a health issue and efforts have been made to monitor and reduce this (Linde & Bruce, 1969;Cohen et al, 1975;Hunter, 1976;Whitcher & Piziali, 1977;Korttila et al, 1978;Davenport et al, 1980;Kole, 1990;Henderson & Matthews, 2000;Sitarek et al, 2000;Byhahn et al, 2001). There have been reports of adverse effects including neurotoxicity, hepatotoxicity and spontaneous abortion among anaesthetists and other exposed medical workers (Belfrage et al, 1966;Klatskin & Kimberg, 1969;Grimmeisen, 1973;Corbett et al, 1974;Popova et al, 1980;Duvaldestin et al, 1981;Neuberger et al, 1981;Keiding et al, 1984;Lings, 1988;Franco, 1989;Luchini et al, 1996).…”
Section: Anaestheticsmentioning
confidence: 99%